2016
DOI: 10.1007/s12149-016-1089-4
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG uptake by rectal cancer is similar in mucinous and nonmucinous histological subtypes

Abstract: Metabolic parameters at baseline PET/CT for patients with rectal cancer are similar in mucinous and nonmucinous histological subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In the present study, as the patients could receive adjuvant chemotherapy according to the postoperative tumour stage after curative resection of the primary tumour, we tried to make up for the limitations of our study by excluding patients with stage IV cancer from the study 30 . In addition, a previous study by Dos Anjos et al 31 demonstrated that there was a signi cant difference in MTV and TLG, although there was no signi cant difference in SUVmax between mucinous and non-mucinous histological subtypes. This could be explained by the fact that histologic subtypes, such as mucinous or signet-ring cell adenocarcinoma, have characteristic features, such as pools of extracellular mucin, and are more likely to reach a higher pT stage than classical adenocarcinoma 3,9,32 .…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, as the patients could receive adjuvant chemotherapy according to the postoperative tumour stage after curative resection of the primary tumour, we tried to make up for the limitations of our study by excluding patients with stage IV cancer from the study 30 . In addition, a previous study by Dos Anjos et al 31 demonstrated that there was a signi cant difference in MTV and TLG, although there was no signi cant difference in SUVmax between mucinous and non-mucinous histological subtypes. This could be explained by the fact that histologic subtypes, such as mucinous or signet-ring cell adenocarcinoma, have characteristic features, such as pools of extracellular mucin, and are more likely to reach a higher pT stage than classical adenocarcinoma 3,9,32 .…”
Section: Discussionmentioning
confidence: 84%
“…For the detection of residual cancer tissue, PET-CT findings present sensitivity of 93% and specificity of 53% and overall accuracy of 85% [3]. The accuracy of PET-CT in the prediction of cCR reaches 96% if it is combined with clinical evaluation [48].…”
Section: Positron Emission Tomography/computed Tomography (Pet/ct)mentioning
confidence: 99%
“…Considering the fact that a metabolic CR is not equivalent to pCR in all cases, several aspects are being assessed to increase the value of PET-CT (e.g., the metabolic tumor volume; the total lesion glycolysis (TLG) and change of its percentage; a reduction in the maximal SUV by applying variable interval periods) [7,48].…”
Section: Positron Emission Tomography/computed Tomography (Pet/ct)mentioning
confidence: 99%
“…The use of fluoro-2-deoxy-D-glucose (FDG) allows for the estimate of tissue metabolism (standard uptake values [SUV]) within areas of interest, and fused images of PET and CT may indicate precise anatomical areas of residual cancer cells, even among mucinous histological subtypes. 54 Most of the available studies have focused on SUV variation for the identification of complete responders to nCRT using variable interval periods and sequential PET/CT imaging. 22,55,56 Accuracies, however, have been insufficient for its routine recommendation into clinical practice.…”
Section: Radiological Assessmentmentioning
confidence: 99%